(untitled) - Vogl, Frank (Chicago, 1996)
Contents: BOOM and the New Industrial Revolution; Risks, Values, and Opportunities; Doing Business in the 2st Century
Keywords: Economic development,Developing countries,Phát triển kinh tế,Phát triển quốc gia; Economic conditions,Điều kiện kinh tế